2013
DOI: 10.1177/1753193413496177
|View full text |Cite
|
Sign up to set email alerts
|

Scaphocapitate arthrodesis for treatment of late stage Kienböck disease

Abstract: Symptomatic lunate collapse owing to Kienböck disease is difficult to treat. To define the potential role of scaphocapitate arthrodesis, we reviewed ten patients who underwent scaphocapitate arthrodesis for stage IIIB-IV Kienböck disease at a mean follow-up of 8.75 years (range 1.3-18.6). Clinical variables included ranges of motion, grip strength, pain, return to work, and QuickDASH (disabilities of the arm, shoulder and hand) scores. Radiographs were evaluated for union, carpal height, alignment, ulnar trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(61 citation statements)
references
References 31 publications
8
53
0
Order By: Relevance
“…In conclusion, this study confirmed our hypothesis concerning the long-term results of scaphocapitate arthrodesis with lunate excision for the treatment of advanced Kienböck's disease. This series has a mean follow-up of 10.7 years, with a maximum follow-up of more than 22 years, superior or comparable with the recent series of Luegmair and Saffar (2014) and Rhee et al (2015). With 90% satisfied patients, absent or minimal pain, a functional arc of mobility and preserved grip strength, we have found this procedure is a reliable and durable solution in this condition.…”
Section: Discussionsupporting
confidence: 63%
“…In conclusion, this study confirmed our hypothesis concerning the long-term results of scaphocapitate arthrodesis with lunate excision for the treatment of advanced Kienböck's disease. This series has a mean follow-up of 10.7 years, with a maximum follow-up of more than 22 years, superior or comparable with the recent series of Luegmair and Saffar (2014) and Rhee et al (2015). With 90% satisfied patients, absent or minimal pain, a functional arc of mobility and preserved grip strength, we have found this procedure is a reliable and durable solution in this condition.…”
Section: Discussionsupporting
confidence: 63%
“…In the past few years, it was found that many types of limited wrist arthrodesis could help treat Kienbock's disease, and partial surgical methods such as STT or CS fusion could effectively eliminate interaction between the scaphoid and distal carpal bones. Therefore, these were considered to be effective means of reducing lunate loading [8][9][10]13) . Van den Dungen et al 21) and Tatebe et al 22) thought that these two surgeries played a role in stabilizing the wrist, as well as reducing lunate loading, and were the best options for treatment of Kienbock's disease.…”
Section: Resultsmentioning
confidence: 99%
“…Surgery for stage IIIb varies, and commonly used treatments include necrotic lunate revascularization, ulnar shortening surgery, and partial carpal fusion [5][6][7] . Studies showed that scaphotrapeziotrapezoid (STT) 8) fusion and capitoscaphoid (CS) 9,10) partial fusion surgery could effectively eliminate interaction between the scaphoid and distal carpal bones, and were considered to be an effective means of reducing lunate loading and the rate of lunate necrosis. The present study used fresh frozen upper extremities of adult cadavers to compare biomechanical changes using STT fusion and CS fusion for stage IIIb lunate necrosis, to determine a more appropriate surgical approach.…”
Section: Introductionmentioning
confidence: 99%
“…Scaphocapitate (SC) fusion was first described by Sutro 29 for scaphoid nonunion using an open technique, and there have been several series since. [30][31][32] Scaphotrapezial trapezium (STT) and SC fusion both transfer the load from the central column to the radial column, therefore unloading the necrotic fragmented lunate which may in turn relieve the pain and progression of KD. 33,34 The SC fusion is indicated for advanced disease of the lunate (B3), or the compromised wrist, including central column degeneration (C1a and C1b) and proximal carpal row instability (C2).…”
Section: Arthroscopic Scaphocapitate Fusionmentioning
confidence: 99%